Pengaruh Pengetahuan Wajib Pajak, Sanksi Perpajakan, dan Kesadaran Wajib Pajak terhadap Kemauan Membayar Pajak pada Wajib Pajak Orang Pribadi (Studi Kasus pada Mahasiswa STIE Eka Prasetya Medan) - Tri Wulandari; Muammar Rinaldi; Yuwanti Anlikie (Outline Journal of Management and Accounting, 2022)
This research aims to know the effect of Taxpayer Knowledge, Tax Sanctions, and Taxpayer Awareness on Willingness to Pay Taxes partially and simultaneously on Individual Taxpayers (Case Study on STIE Eka Prasetya Medan Student). The population used in this research were students of class 17, class 18, and class 19 STIE Eka Prasetya Medan, totaling 845 people. Samples were taken as many as 90 respondents using the Slovin formula. The results of partial hypothesis testing show that Taxpayer Knowledge has a significant effect on Willingness to Pay Taxes. The results of partial hypothesis testing show that Tax Sanctions have no effect and are not significant on Willingness to Pay Taxes. The results of partial hypothesis testing show that Taxpayer Awareness has a significant effect on Willingness to Pay Taxes. The results of simultaneous hypothesis testing show that Taxpayer Knowledge, Tax Sanctions, and Taxpayer Awareness have a significant effect on Willingness to Pay Taxes. The results of the coefficient of determination shows that 49,1% Willingness to Pay Taxes can be explained by Taxpayer Knowledge, Tax Sanctions, and Taxpayer Awareness, while the remaining 50,9% is explained by other variables such as Taxpayer Environment, Quality Services, and Perceptions of the Effectiveness of the Taxation System.